Проблемні питання та основні напрями удосконалення та розвитку національної інфраструктури відкритого ключа - Горбенко, Ю. І.; Чичмар, С. В.; Тоцький, О. С.; Бондаренко, В. І.; Горбенко, І. Д. (ХНУРЭ, 2011)
An analysis of the development and use of public key infrastructure in Ukraine, are considered key issues for improvement and standardization of various applications, substantiated requirements for public key certification policies and perspective cryptographic conversions.
Keywords: відкритий ключ; електронний документообіг